2019
DOI: 10.3389/fmicb.2019.00617
|View full text |Cite
|
Sign up to set email alerts
|

Cyanophage Propagation in the Freshwater Cyanobacterium Phormidium Is Constrained by Phosphorus Limitation and Enhanced by Elevated pCO2

Abstract: Intensification of human activities has led to changes in the availabilities of CO 2 and nutrients in freshwater ecosystems, which may greatly alter the physiological status of phytoplankton. Viruses require hosts for their reproduction and shifts in phytoplankton host physiology through global environmental change may thus affect viral infections as well. Various studies have investigated the impacts of single environmental factors on phytoplankton virus propagation, yet little is known… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 83 publications
(113 reference statements)
1
18
0
Order By: Relevance
“…These conditions primarily affect host physiology, and thereby may influence virus replication or infection success. For example, earlier work has shown that under resource limitation host growth can be constrained, thereby prolonging virus latent period and/or resulting in a reduced burst size Cheng et al 2019). Warming has been reported to stimulate host growth rates and, as such, virus production (Steenhauer et al 2016;Demory et al 2017;Maat et al 2017).…”
mentioning
confidence: 99%
“…These conditions primarily affect host physiology, and thereby may influence virus replication or infection success. For example, earlier work has shown that under resource limitation host growth can be constrained, thereby prolonging virus latent period and/or resulting in a reduced burst size Cheng et al 2019). Warming has been reported to stimulate host growth rates and, as such, virus production (Steenhauer et al 2016;Demory et al 2017;Maat et al 2017).…”
mentioning
confidence: 99%
“…This founding contributes as an important indicator of the interference of these phages in the environment, known for their ability to perform photosynthesis by consuming oxygen and their potential for binding to nitrogen or production of toxins [31]. Nitrogen or phosphorus supplies, in addition to reduced growth rate and biomass, may naturally limit freshwater ecosystems, including those involving cyanobacteria accumulation [35].…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 25% of all virus‐like particles (viruses that have not been cultured to determine host specificity) in the Gulf of Mexico are specific to the planktonic cyanobacterium Synechococcus (discussed in Hewson, O'Neil, & Dennison, 2001). There is limited information on viruses targeting benthic proliferations (Cheng, Frenken, Brussaard, & Van de Waal, 2019; Hewson et al, 2001; Voorhies et al., 2016). Of the few studies on benthic proliferations, Hewson et al.…”
Section: Mitigationmentioning
confidence: 99%
“…(2001) identified virus‐like particles that were associated with a decline in Lyngbya majuscula Harvey ex Gomont in Moreton Bay, Australia, noting that further research was needed to understand the consequences of cyanophage‐mediated collapse within these communities. Additionally, Cheng et al (2019) assessed cyanophage infection through alterations in environmental stressors (phosphorus limitation and elevated pCO 2 ) in Phormidium . They also found that cyanophage adsorption and production rate was greater under moderate phosphorus limitation in combination with elevated pCO 2 levels, these results suggest that viral propagation and activation could increase as CO 2 levels rise.…”
Section: Mitigationmentioning
confidence: 99%